Foundation Fieldbus Interoperability Test, System Development and Configuration - Foxboro (Dissertation) - Mohd Syazwan Mohd Zaki, Mohd Syazwan (2009)

(untitled)
Fieldbus is a network technology designed to improve overall process or system efficiency in contrast to the current 4-20mA network. Verification of the system interoperability and reliability, including stress test is important for it to be accepted and applicable in the industry. A proper methodology justification and an outline of the methodological approach of the interoperability, reliability and stress test in order for it to be executed within the scope of study and given time frame are elaborated in this report. Segment design validation simulated using P+F Segement Checker with High Power Trunk (HPT) concept.